Organization of accounting and analysis at small enterprises of the tourist industry - Pererva, P. G. (My University, 2020)
The report proves that the methodology for evaluating management decisions in managing the costs of a tourism enterprise is quite simple to calculate and effective. Using this methodology, it is possible to analyze future prospects and the current state of activity.
Організація обліку та аналізу на малих підприємствах туристичної галузі
Keywords: methodology; management; analysis; accounting; tourism enterprise